IoT in Small-Scale Farming: A Systematic Review of Socio-Economic Outcomes and Future Directions - Moveh, Fred Fudah; Mohammad , Abba Jalo; Kadams, Adaiti Allen; Mohammed, Abulfatahi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
In recent years, the Internet of Things (IoT) has been changing how farming works worldwide, giving farmers real-time access to data, improving precision farming, and helping them make better decisions. But in many developing countries, small-scale farmers are still faced with challenges like limited finances, poor digital skills, and weak infrastructure, making it hard for them to adopt these technologies. This study set out to understand why this gap exists. By reviewing 50 scholarly journal articles, the research identifies key socio-economic barriers that limit IoT adoption in agriculture, especially among small-scale farmers. The study brings new knowledge by highlighting four critical areas that need attention: financial inclusion, digital literacy, market access, and supportive policies. It also shares real-world examples of how IoT is being used in different developing regions, providing insights that haven’t been widely discussed in earlier research. Findings show that while IoT can help farmers increase productivity, use resources more efficiently, and improve their profits, adoption remains low mainly because of the high costs, poor infrastructure, and lack of technical know-how. This research contributes to existing knowledge by providing practical recommendations such as offering financial support, training programs, and policy reforms as key steps to help small-scale farmers in the adoption of IoT solutions. By focusing on the real challenges farmers face and offering practical, region-specific suggestions, this study adds a socio-economic perspective to the growing conversation about digital farming. The insights from this work are intended to help policymakers, technology providers, and development organizations make smarter decisions when designing IoT solutions for small-scale farmers in developing countries.